2017
DOI: 10.1002/lary.26442
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of pain improves specificity of clinical diagnostic criteria for adult chronic rhinosinusitis

Abstract: 4. Laryngoscope, 127:1011-1016, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 54 publications
0
25
1
Order By: Relevance
“…Some studies have demonstrated poor association with chronic rhinosinusitis, as related symptoms may be nonspecific. 3 - 6 For example, authors have suggested that facial pain, dental pain, ear pain, and headache could be removed from diagnostic criteria without significant changes in diagnostic sensitivity. 5 In contrast, other authors have concluded that questionnaire results can have functional sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have demonstrated poor association with chronic rhinosinusitis, as related symptoms may be nonspecific. 3 - 6 For example, authors have suggested that facial pain, dental pain, ear pain, and headache could be removed from diagnostic criteria without significant changes in diagnostic sensitivity. 5 In contrast, other authors have concluded that questionnaire results can have functional sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“… 3 - 6 For example, authors have suggested that facial pain, dental pain, ear pain, and headache could be removed from diagnostic criteria without significant changes in diagnostic sensitivity. 5 In contrast, other authors have concluded that questionnaire results can have functional sensitivity and specificity. 45 Prior studies have also demonstrated that even within a single validated instrument, results may be mixed, with SNOT-22 nasal domain scores performing better than overall scores, 7 - 10 , 21 - 26 , 42 also suggesting that specific approaches to symptoms and symptom clusters can alter discriminatory capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraine is associated with rhinorrhea and nasal congestion due to sinonasal neurogenic stimulation in 50–60% of people, leading to misdiagnosis of CRS in the absence of objective evidence of sinus disease. 37, 38 However, migraine is also co-morbid with CRS 39 and can also influence timing of surgical management. 40 We suspect that co-morbidity and misdiagnosis may each be occurring.…”
Section: Discussionmentioning
confidence: 99%
“…Data from cohort studies show that orofacial pain is a poor predictor of chronic rhinosinusitis, and patients are more likely to be misdiagnosed if pain is used as a criterion to screen patients for rhinosinusitis 6789. A prospective observational study involving 108 patients with confirmed chronic rhinosinusitis found that less than a third of patients had orofacial pain 7.…”
Section: What Are the Common Causes Of Orofacial Pain?mentioning
confidence: 99%